2019
DOI: 10.1002/ejsp.2599
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness meditation is associated with decreases in partner negative affect in daily life

Abstract: Eur J Soc Psychol. 2020;50:35-45. | 35 wileyonlinelibrary.com/journal/ejsp | INTRODUC TI ONResearch on mindfulness meditation has, to date, focused almost wholly on the intrapersonal effects of meditation practice. Numerous reviews and meta-analyses collate the myriad cognitive, emotional, and physiological consequences of meditation practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
(61 reference statements)
0
16
0
1
Order By: Relevance
“…One study included not only couples but also dyads that were in daily contact, such as roommates and close friends. In this sample, 37.1% were in a romantic relationship (May et al, 2020). Overall, the average relationship duration was M = 12.42 years as reported in six studies (standard deviation reported only in two studies, SD = 14.35).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…One study included not only couples but also dyads that were in daily contact, such as roommates and close friends. In this sample, 37.1% were in a romantic relationship (May et al, 2020). Overall, the average relationship duration was M = 12.42 years as reported in six studies (standard deviation reported only in two studies, SD = 14.35).…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Table 2, differential effects between partners emerged: While some studies revealed benefits for both partners (Birnie et al, 2010; Khaddouma et al, 2017), others reported benefits only for one partner (Berk et al, 2019; Gambrel & Piercy, 2015a). If only one partner was enrolled in the intervention, mindfulness increased more notably for them compared with their partners (Khaddouma et al, 2017; May et al, 2020). Similarly, only the meditating partner noted a significant increase in the facets of mindfulness as measured with the FFMQ (May et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were no such effects for positive behaviours. In line with this, May et al [39] found that mindfulness meditation practice was associated with a decrease in partner negative affect, but no increase in positive affect, showing that mindfulness may be more effective in reducing negative experiences than enhancing positive ones.…”
Section: Attachment Rm and Same-day Behavioursmentioning
confidence: 80%
“…Experiencing higher RM on a given day may also prevent one’s own attachment insecurity from undermining partner relationship behaviours. Research has found that one partner’s mindfulness lowers the other partner’s dominance and reactivity during relationship conflict [ 38 ] and negative affect [ 39 ]. Additionally, Kimmes et al [ 9 ] found that actor RM predicted better partner relationship quality and general wellbeing.…”
Section: Introductionmentioning
confidence: 99%